(untitled) (Research, Society and Development, 2022)
Introduction: Rapid immunochromatographic tests, quick and easy-to-run, are an important tool in the diagnosis of SARS-CoV-2, but its effectiveness rate varies depending on the manufacturer, being necessary to identify the factors that can influence the performance of these tests, when compared to the gold standard, RT-PCR. Objective: To explain the main evidence on the performance of rapid tests, pointing the main studies that evidence the antigen detection and discussing immunochromatographic methods performance compared to molecular trials in COVID19 diagnosis. Methodology: Exploratory and descriptive electronic bibliographic review carried out through searches in the databases of the Virtual Health Library (BVS), Scientific Library Online (SciELO) and PUBMED search platform, using the descriptors "COVID-19", "SARS- CoV-2”, “lateral flow”, “immunochromatography”, “rapid test”, “performance”, “evaluation”, “precision”, “comparison” and “antigen”, followed by application of inclusion and exclusion criteria relevant to the study. Results: Among the 20 studies selected in the final sample (E1 to E20), considerable variation in sensitivity (24.3% to 100%) and lower variation in specificity (86% to 100%) were observed in the tests evaluated, and the main variables analyzed that could affect its performance are: patient factors, quality of sample processing and test operator. Conclusion: Lateral flow antigen immunoassays have the advantage of indicating active disease, however, their use requires caution, especially in asymptomatic patients in which the test has decreased sensitivity.